2013
DOI: 10.1590/s0100-204x2013000800041
|View full text |Cite
|
Sign up to set email alerts
|

Vitamina A em dieta de juvenis de pacu cultivados em tanques-rede

Abstract: O objetivo deste trabalho foi avaliar o efeito da suplementação de vitamina A na alimentação de juvenis de pacu cultivados em tanques-rede. Foram utilizados 2.000 peixes, com peso inicial médio de 66,93±15,03 g, distribuídos em delineamento inteiramente casualizado, em 20 tanques-rede de 5,0 m³, com cinco tratamentos e quatro repetições. As rações foram formuladas com 0, 3.000, 6.000, 9.000 e 12.000 UI de vitamina A por quilograma de dieta, por meio da suplementação com acetato de retinol. O arraçoamento foi r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 20 publications
(31 reference statements)
2
6
0
Order By: Relevance
“…Studies that evaluated vitamin A dose responses report that mortality is common when there is a vitamin A deficiency in the diets (ORNSRUD et al, 2002;HU et al, 2006;PEIL et al, 2007;CAMPECHE et al, 2009). In this study, the presence or absence of vitamin A supplementation in the diet did not interfere with the survival of pacus, which corroborates the data observed by SIGNOR et al (2013) in the same species. Likewise, GUO et al (2010) did not observe an effect of vitamin A supplementation in the diet on the survival of tilapia fingerlings; these authors observed 98.57% survival in fish that received a diet without vitamin A supplementation.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Studies that evaluated vitamin A dose responses report that mortality is common when there is a vitamin A deficiency in the diets (ORNSRUD et al, 2002;HU et al, 2006;PEIL et al, 2007;CAMPECHE et al, 2009). In this study, the presence or absence of vitamin A supplementation in the diet did not interfere with the survival of pacus, which corroborates the data observed by SIGNOR et al (2013) in the same species. Likewise, GUO et al (2010) did not observe an effect of vitamin A supplementation in the diet on the survival of tilapia fingerlings; these authors observed 98.57% survival in fish that received a diet without vitamin A supplementation.…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, the authors indicated that further research was needed to evaluate the influence of vitamin A on growth performance in pacu. On the other hand, BUENO et al (2008) reported that the environment used by the researchers in that study (SIGNOR et al, 2013) was oligotrophic, which may have compromised the study results. Knowledge about the effects of vitamin A on fish growth is essential for de designing of diet formulations that meet the nutritional requirements of fish (NRC, 2011).…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…In the same location (Itaipu reservoir), Hilbig et al (2012) suggested a decrease in 30% of the total feeding supply for Pacu production in a fish cage. Other studies that guarantee profitability of Pacu production in fish cages located in reservoirs have also been performed, approaching nutrition, production indexes and the minimum scale of Pacu farming (Silva et al, 2012;Signor et al, 2013).…”
Section: Regulations and Main Species Produced In Fish Cages In Brazilmentioning
confidence: 99%